[Zestaw znaczków z Matką Boską Częstochowską i Ostrobramską oraz modlitwą za niepodległość Polski i Litwy] . Set of unofficial stamps with Our Lady of Częstochowa and Our Lady of the Gate of Dawn in support for national independence of Poland and Lithuania - Poczta Solidarności Walczącej. (Poczta Solidarności Walczącej, 1985)
Black and red or black, red, green and yellow print on white paper, without perforation. Stamps, with "Poczta Solidarności Walczącej" imprint, represent the Catholic devotion and national aspirations of Poland and Lithuania. Each stamp consists of an image of a national religious icon of Virgin Mary (Our Lady of Częstochowa and of the High Gate respectively), national emblems and colors of the country and a caption (bilingual in case of Lithuania) with a prayer for national independence. Price range: 60-90 zł